Inequalities for upper bounds of functionals on the classes $W^r H^{ω}$ and their applications - Babenko, V. F.; Korneichuk, N. P.; Kofanov, V. A.; Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We show that the well-known results on estimates of upper bounds of functionals on the classes $W^r H^{ω}$ of periodic functions can be regarded as a special case of Kolmogorov-type inequalities for support functions of convex sets. This enables us to prove numerous new statements concerning the approximation of the classes $W^r H^{ω}$, establish the equivalence of these statements, and obtain new exact inequalities of the Bernstein-Nikol’skii type that estimate the value of the support function of the class $H^{ω}$ on the derivatives of trigonometric polynomials or polynomial splines in terms of the $L^{ϱ}$ -norms of these polynomials and splines.